The World Council of Churches Assembly in New Delhi 1961 and the German Democratic Republic: - Frieder Ludwig (Revista de História da Sociedade e da Cultura)
The Third Assembly in New Delhi in November/December 1961 marked a watershed in the process of de-Westernisation for the World Council of Churches (WCC), an ecumenical umbrella body founded in Amsterdam in 1948. The acceptance of the Russian Orthodox Church, as well as other Eastern Orthodox Churches, into membership, the integration of the International Missionary Council into the WCC and the stronger representation of African, Asian and Latin American Churches made the Assembly a crucial event.